1985
DOI: 10.1093/nar/13.24.8927
|View full text |Cite
|
Sign up to set email alerts
|

Base pairing involving deoxyinosine: implications for probe design

Abstract: The thermal stability of oligodeoxyribonucleotide duplexes containing deoxyinosine (I) residues matched with each of the four normal DNA bases were determined by optical melting techniques. The duplexes containing at least one I were obtained by mixing equimolar amounts of an oligonucleotide of sequence dCA3XA3G with one of sequence dCT3YT3G where X and Y were A, C, G, T, or I. Comparison of optical melting curves yielded relative stabilities for the I-containing standard base pairs in an otherwise identical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
225
1
8

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(257 citation statements)
references
References 23 publications
21
225
1
8
Order By: Relevance
“…The C/I base pair has the highest level of stability, in keeping with its structural similarity to a C/G base pair (34). The outcome of the computational analysis on the stability of the hypoxanthinecontaining base pairs is consistent with experimental analyses previously reported (35)(36)(37). The stability of the base pairs as estimated by the PMF calculation suggests that the G/I base pair is more prone to base flipping.…”
Section: Discussionsupporting
confidence: 81%
“…The C/I base pair has the highest level of stability, in keeping with its structural similarity to a C/G base pair (34). The outcome of the computational analysis on the stability of the hypoxanthinecontaining base pairs is consistent with experimental analyses previously reported (35)(36)(37). The stability of the base pairs as estimated by the PMF calculation suggests that the G/I base pair is more prone to base flipping.…”
Section: Discussionsupporting
confidence: 81%
“…A rate-limiting nucleotide flipping step for Hx excision would also explain the base pair specificity observed previously (16,20). Hypoxanthine is excised more slowly from a more stable Hx⅐C Watson-Crick type pair than an Hx⅐T wobble pair (31)(32)(33). Two explanations are possible to explain why excision of ⑀A is not affected to a great degree by its base pairing partner.…”
Section: Effects Of Hydrogen Bonding Within a Basementioning
confidence: 84%
“…It has a similar structure to guanosine, but lacks the 2-amino group, and pairs with the natural bases as shown in Figure 1 (2)(3)(4)(5)(6)(7)(8)(9). Deoxyinosine has been investigated as a universal base for use in oligonucleotide probes and primers (10)(11)(12). Martin et al using an optical melting technique concluded that it does not pair equally with the four naturally occurring bases, the thermodynamic stabilities being in the order I-C > I-A > I-G -I-T.…”
Section: Introductionmentioning
confidence: 99%